Identifying female mobile bully-victim characteristics in selected high schools in South Africa: towards an anti-bullying mobile application - Adeyeye, Oshin Oluyomi (Department of Information Systems, 2020)
Within the majority of learners' years in high school, bullying is one common experience that pervades those years of transitioning to adulthood. The bullying phenomenon has been studied over a few decades and we have basically come to understand that bullying is any situation where a perpetrator, over a period, continually behaves aggressively towards another individual who cannot defend themselves; here an imbalance of power is accentuated. This has been studied in recent years with the increasing reports of fatalities among high school learners who have resorted to suicide and self-harm as a solution. In the current digital age, the extent of bullying is faster and reaches further, and as such, more dynamics seem to be involved in the mix. The role of technology in improving the way we live and do things has also extended to the way crimes and injustice are being meted out in society. Youths and adolescents, particularly high school learners have been noted to have a phenomenal adoption of technology. They are also noted to increasingly acquire the most updated mobile technology devices and are therefore a fit sample for examining mobile bullying. In addition, more studies are finding out distinct classifications such as bully, victim and bully-victims, with the bully-victim studies just beginning to gain attention. As with the more familiar traditional bullying, fundamental psychological, social and economic factors largely predict the exhibiting of bully-victim characteristics. Some studies have found that the consequences are, however, more severe within the group but not without some inconsistencies in findings; hence the need to investigate and begin to proffer the right interventions or solutions. This current study set out to investigate characteristics of female mobile bully-victim behaviours amidst claims that they are a minority and so no special attention need be given to them. A pilot study, conducted by this researcher, examining the bully-victim subgroup from previous cyberbullying research studies (Kabiawu & Kyobe, 2016), found the group exists and is fast gaining more popularity in research. Further examination of literature found the discourse around age factor in prevalence, with gender variances, interventions, and country differences, among others. Many of the past studies on gender variance enquiries were conflicting, interventions were largely not technology-oriented, and studies were mostly from outside the continent of Africa. This stirred up the interest in studying female mobile bully-victims in South African high school students and the exploration of a general (i.e. non-gender-specific) technical intervention. The study followed a pragmatic philosophy and mixed method in collecting and analyzing the data. The study was carried out in Cape Town, South Africa; eight schools agreed to participate in the survey, and 2632 responses were collected from a range of schools (consisting both public and independent schools). Of these, 911 were females and 199 bully-victims, placing the group in a minority position. This maintained the keen interest in understanding the issues that face them rather than overlooking the subgroup as some studies would argue. Additionally, the study vii entailed the development of an IT artefact in the form of a mobile application, called “The BullsEye!” through a Design Science process. The aim of the artefact was to proffer a technical intervention and observe the usefulness of the artefact in dealing with general bullying as well as for addressing, mitigating and providing support for bullying. The study collected information quantitatively to explore the differences in age, school grade, type of school, family type, ethnicity and perceptions of interventions from students. This process was also used to recruit interested students in designing the mobile app intervention to address the secondary aspect of the research. The study predicted that at different ages and school grades, female mobile bullyvictim behaviours would be different. It also proposed that these behaviours exhibited by bully-victims would differ when the school type, ethnicity and family from which students come, are compared. When interventions by teachers, family and friends were compared, the study predicted that the female bully-victim behaviours exhibited would not be same, depending on the perception of the level of intervention the students received. These hypotheses were tested empirically using quantitative methods to check the analysis of the variance of the mean scores of the collected data. The results of the analysis of variance showed findings that resulted in some partial and some strong acceptance of the hypotheses. As expected, there were age and grade differences observed among the behaviours of the female bully-victims surveyed. The younger in age and grade these students were, the more of the behaviours were found to be exhibited by them. Students from conventional families with two parents were expected to exhibit fewer female bully-victim characteristics, but this was not necessarily the finding in the study and inconsistent with most previous studies. The prediction on ethnicity was also partially accepted due to mixed indications according to findings. Establishing the respondents' ethnicity showed a group of students who did not wish to reveal their ethnicity but were rife in bully-victim behaviour via phone calls, email and SMS's. This raised a question of whether their societal status affected their behaviour. The type of school was also found not to accurately predict female bully-victim behaviours in this study as expected or in accordance to majority of existing literature. There was, however, evidence of a distinct social media mechanism of bullying/victimization peculiar to an Independent school in relation to other schools. The prediction on interventions, while being partially supported, provided a useful insight into strengthening the need to appreciate and continually invest in the quality of interventions provided to address mobile bullying. Generally, the findings revealed that female mobile bully victims had significantly higher experience of being victims (i.e. had been bullied) than those who were not. This may be due to failings in the provision for reporting issues or the way reports are being handled, which is another useful insight into interventions. The artefact designed as an intervention in this study also showed high acceptance of the app. This can be attributed to the fact that the design process followed a methodology that is grounded in practice and in the body of knowledge. This was embellished by emerging methodologies of involving the intended users, though schoolchildren, in the evolution of the artefact design. The implication of these findings is that there may be current frameworks addressing female mobile bully-victim behaviour at school and family levels; however, focus of interventions should be on teaching the right culture with regards to mobile phone use. This gives credence to the second objective of this study, which was to design a digital intervention. The artefact was designed to empower victims and bystanders, the purpose of which seemed to have been achieved with a high rate of approval for the app. The knowledge gained from this phase, despite the limitations, points that visual appeal is important when designing for high school students. It also showed that students are interested in learning in an environment free of adult presence or supervision. However, many more strategies and principles can be applied to intervene from different perspectives to create a more wholistic solution. This knowledge is useful for future works that seek to include their input in design process. The understanding of these characteristic mechanisms is important in proffering relevant interventions as the distinct female bully-victim group is newly gaining attention. This is useful in theory development, especially feminist theories on violence as well as where and how to target interventions. This impacts practice in terms of knowledge of how female mobile bully-victims operate and how one can begin to empower them to protect themselves and reflect on their online and mobile phone behaviour. Therefore, for Information Systems practice, this study provides a worthwhile contribution, especially in answering questions such as, what information systems and interventions should be developed and how to maximize such systems for their intended learning purposes. From the lessons learned in this study, the research also contributes by proposing considerations for future and further research.